Performance of a two-stage anaerobic digestion system treating fruit pulp waste: The impact of substrate shift and operational conditions. (August 2018) - Carvalheira, Mónica; Cassidy, Joana; Ribeiro, João M.; Oliveira, Bruno A.; Freitas, Elisabete B.; Roca, Christophe; Carvalho, Gilda; Oehmen, Adrian; Reis, Maria A.M.
Highlights: Two-phase anaerobic digestion was successfully applied to treat fruit pulp wastes. Acidification degrees above 60% were obtained despite the feedstock change. High methane productivities (4.33 LCH4 /(L.d)) and content (70%) were achieved. COD removal up to 99% was obtained. High organic loading rate efficiently applied, thus a higher wastewater volume can be treated. Abstract: Food and beverage industry wastes present high amounts of organic matter, which may cause water quality degradation if not treated. Two-stage anaerobic digestion is a promising and efficient solution for the treatment of this type of wastes whilst producing bioenergy. The composition of fruit pulp waste varies throughout the different harvesting seasons, which may impact the process performance. In this study, a two-stage anaerobic digestion system was operated to assess the effect of substrate shift from peach to apple pulp wastes (obtained from a fruit juice company) on the microbial community activity and performance. During acidogenesis, the sugar conversion was higher than 95% for all operational conditions tested, obtaining a degree of acidification up to 89%. Principal Component Analysis was used to evaluate the relationship between the initial fermentation state of the residues in each operational condition and the obtained effluent. Methanogenic activity resulted in high organic carbon consumption (89%) and high methane productivities, achieving a maximum of 4.33 L C H 4 / L . d for peach waste influent. Overall, the results showed that the microbial community activity was not affected by the substrate shift, converting the sugars into biogas rich in methane (>70% CH4 ). Microbial analysis showed that the communities present in the acidogenic and methanogenic reactors were highly enriched in bacteria and archaea, respectively. The observed stability of the process, also demonstrated in pilot scale, confirmed the robustness of the process and thus, was suitable for implementation in companies producing seasonally different fruit wastes in a continuous operation.